Gyrfalcons and Ptarmigan in a Changing World 2011
DOI: 10.4080/gpcw.2011.0209
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Biology of Gyrfalcons in Greenland.

Abstract: ABSTRACT.-We studied two breeding populations of Gyrfalcons (Falco rusticolus) approximately 1,200 km apart in Greenland. During 1998-2006, we collected data from a population in the central-west (Kangerlussuaq), and during 1994-2006 and 2008-2010 from a population in the northwest (Thule). Gyrfalcons in Kangerlussuaq bred approximately 18 days earlier than those in Thule, with egg laying, on average, starting on 17 April and 5 May, respectively. Reproduction was similar between areas, with no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…), particularly during the early breeding season when prey are limited. In Kangerlussuaq, Gyrfalcon lay date from 1998 to 2006 ranged from 28 March to 9 May (mean = 17 April; Burnham & Burnham ), with Rock Ptarmigan Lagopus muta , Snow Bunting Plectrophenax nivalis and Arctic Hare Lepus arcticus being the primary prey available early in the breeding season (Salomonsen , Boertmann , K. Burnham unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), particularly during the early breeding season when prey are limited. In Kangerlussuaq, Gyrfalcon lay date from 1998 to 2006 ranged from 28 March to 9 May (mean = 17 April; Burnham & Burnham ), with Rock Ptarmigan Lagopus muta , Snow Bunting Plectrophenax nivalis and Arctic Hare Lepus arcticus being the primary prey available early in the breeding season (Salomonsen , Boertmann , K. Burnham unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
“…Using similar sampling years, the timing of Gyrfalcon nest initiation was approximately 18 days earlier in Kangerlussuaq (mean lay date = 107.4, sd = 9.4, n = 70; this study) than in the Thule population c . 1200 km to the north (date = 125.0, sd = 7.0, n = 40; Burnham & Burnham ). The Kangerlussuaq Gyrfalcon population also exhibited a much wider range of dates for the nesting period duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within our study area in the Avanersuaq District, an ameliorating climate has been suggested as a contributing factor to recent increases in both local common eider and peregrine falcon populations, and earlier nest initiation dates for gyrfalcon (Burnham and Burnham 2011;Burnham et al 2012a, b). As daily temperatures increase, the number of days available to breed and successfully raise offspring also increases, thereby allowing for a northward expansion among many species.…”
Section: Possible Mechanisms For Observed Abundance Changesmentioning
confidence: 93%
“…If the research question involves the growth or survival of raptor nestlings, then it is best to survey prey during the brood rearing period. This can depend on the study population in question, but for Gyrfalcons brood rearing generally occurs from late May through early August (Poole and Bromley 1988, Burnham and Burnham 2011, Milligan and Powell 2014. Conversely, one may wish to determine the effects of prey abundance on the occupancy of nest sites, or the prelaying body condition and phenology of breeding adults, or nest abandonment during incubation.…”
Section: Designing and Implementing A Distance Sampling Surveymentioning
confidence: 99%